Teaching and Learning Pronunciation through Instructional Pronunciation Video at Sman 4 Sampolawa - Potto, Mardiana; Jaya, Amir; Siam, Siam (Journal of Teaching of English, 2021)
This research was conducted to find out whether there is a significant effect of using Instructional Pronunciation Video on students’ pronunciation ability at ten grade students of SMAN 4 Sampolawa. The design of the research was quasi-experimental design consisting of experimental and control class. The total population was 42 students which consisted of two classes. The sample of this research was class X.MIA (as the experimental class) consisting of 21 students and class X.IIS (as the control class) consisting of 21 students. The data of this research were obtained by giving pre-test and post-test in the form of pronunciation test to the students. Then, the data were analyzed by using SPSS 16.0 version. The data were analyzed by descriptive statistic and inferential statistic and for testing hypothesis of this research used independent sample t-test. In this research, it was found that the mean score of post-test in experimental class was higher than that of post-test in control class. It signified that there was a significant difference between students’ pronunciation taught by using Instructional Pronunciation Video and without using Instructional Pronunciation Video.